Attitudes toward Assisted Suicide: Does Family Context Matter?. Issue 2 (2nd April 2016) - Frey, Laura M.; Hans, Jason D.
Abstract : Little is known about how family-related contextual variables impact attitudes toward assisted suicide. A probability sample (N = 272) responded to a multiple-segment factorial vignette designed to examine the effects of 6 variables—patient sex, age, type of illness, relationship status, parenthood status, and family support—on attitudes toward physician- and family-assisted suicide. Respondents were more likely to support physician-assisted suicide if they heard about an older patient or a patient experiencing physical pain than a younger patient or one suffering from depression, respectively. For family-assisted suicide, respondent support was higher when the patient had physical pain than depression, and when the patient's spouse or friend was supportive of the wish to die than unsupportive. Attitudes about physician and family obligation to inform others were affected by type of illness, relationship status, family support, and respondent education and religiosity. The experience of pain, motivations for family involvement, confidentiality issues, and physicians' biases concerning assisted suicide are discussed.